(untitled) (MAUSAM, 1954)
The value of lag coefficient of the bimetal thermometer used in chronometric radiosonde of the India Meteorological Department when it is exposed at various orientations to air currents with different speeds has been determined experimentally. The order of errors that may be expected due to lag at different pressure levels has also been computed.